ISSUES OF DIGITAL TECHNOLOGIES AND RENEWABLE ENERGY INTEGRATION - Abduganiyev, Murodzhon Shavkat oglu (THE INNOVATION ECONOMY, 2026)
The article analyzes the issues of integrating digital technologies with renewable energy sources from a scientific, theoretical and practical perspective. In particular, the role of digital platforms, intelligent management systems, data analysis and artificial intelligence technologies in the effective use of renewable sources such as solar and wind energy is highlighted. Also, the importance of digital transformation processes in the context of developing a "green economy" in Uzbekistan is assessed and practical proposals are developed.